2016
DOI: 10.18632/oncotarget.9120
|View full text |Cite
|
Sign up to set email alerts
|

Metformin restores crizotinib sensitivity in crizotinib-resistant human lung cancer cells through inhibition of IGF1-R signaling pathway

Abstract: AimDespite the impressive efficacy of crizotinib for the treatment of ALK-positive non-small cell lung cancer, patients invariably develop therapeutic resistance. Suppression of the IGF-1R signaling pathway may abrogate this acquired mechanism of drug resistance to crizotinib. Metformin, a widely used antidiabetic agent, may reverse crizotinib resistance through inhibition of IGF-1R signaling.ResultsThe present study revealed that metformin effectively increased the sensitivity of both crizotinib-sensitive and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 35 publications
3
29
0
Order By: Relevance
“…IGF‐1R signalling also mediates resistance to EGFR inhibition by TKIs and metformin has been shown to sensitize NSCLC cells that are resistant to EGFR‐inhibiting TKIs . For example, metformin restores crizotinib sensitivity in crizotinib‐resistant human lung cancer cells through inhibition of the IGF‐1R signalling pathway . Metformin has also been reported to reduce temozolomide resistance in glioblastoma cell lines .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…IGF‐1R signalling also mediates resistance to EGFR inhibition by TKIs and metformin has been shown to sensitize NSCLC cells that are resistant to EGFR‐inhibiting TKIs . For example, metformin restores crizotinib sensitivity in crizotinib‐resistant human lung cancer cells through inhibition of the IGF‐1R signalling pathway . Metformin has also been reported to reduce temozolomide resistance in glioblastoma cell lines .…”
Section: Resultsmentioning
confidence: 99%
“…35 For example, metformin restores crizotinib sensitivity in crizotinib-resistant human lung cancer cells through inhibition of the IGF-1R signalling pathway. 36 Metformin has also been reported to reduce temozolomide resistance in glioblastoma cell lines. 37 Paradoxically, a number of TKIs and mTOR inhibitors used in oncology are associated with drug-induced hyperglycaemia.…”
Section: Potential Use In Oncologymentioning
confidence: 99%
“…Moreover, metformin treatment significantly improved the survival of lung cancer patients with epidermal growth factor receptor (EGFR)activating mutations and type 2 diabetes 15 . We also showed that metformin restores crizotinib sensitivity in crizotinibresistant NSCLC cells through the inhibition of the insulinlike growth factor 1 receptor (IGF1-R) signalling pathway 16 . It is worth noting that our previous study found that metformin exerted an inhibitory effect on downstream signalling mediators of MET, such as AKT and ERK 14 , which encouraged us to investigate whether metformin could restore alectinib sensitivity in alectinib-resistant cells with high expression of HGF and MET.…”
Section: Introductionmentioning
confidence: 89%
“…2b). According to the results of our previous study 16 , the in vitro dose of metformin used in this study was 5 mmol/L, which has minimal influence on ALKpositive NSCLC cell growth. Next, we performed the Ki67-incorporation assay and/or the colony-forming assay in H3122/Vec, H3122/HGF, and H3122-AR3 cells.…”
Section: Metformin Reverses the Alectinib Resistance Induced By Hgf/mmentioning
confidence: 98%
“…22 Moreover, metformin can reverse crizotinib resistance by inhibiting type I insulin-like growth factor receptor (IGF-1R) signalling in crizotinib-resistant human lung cancer cells. 23 Metformin and sorafenib can synergistically inhibit tumour growth by activating the AMPK pathway in NSCLC cells both in vitro and in vivo. 24 Thus, combination of metformin with other chemotherapy agents may improve treatment outcome for NSCLC patients.…”
Section: Introductionmentioning
confidence: 99%